Oxidative stress, DNA damage and antioxidant enzyme activities in the pacific white shrimp (Litopenaeus vannamei) when exposed to hypoxia and reoxygenation. (February 2016) - Li, Yuhu; Wei, Lin; Cao, Jiangrong; Qiu, Liguo; Jiang, Xiu; Li, Ping; Song, Qinqin; Zhou, Hailong; Han, Qian; Diao, Xiaoping
Abstract: To evaluate the genotoxic and physiological effects of acute hypoxia on the pacific white shrimp ( L. vannamei ), shrimps were treated firstly with three dissolved oxygen levels 6.5 ppm (control), 3.0 ppm and 1.5 ppm for 24 h, respectively, and then reoxygenated (6.5 ppm) for 24 h. The changes of superoxide dismutase (SOD) activity, glutathione peroxidases (GPX) activity, malondialdehyde (MDA) concentration and DNA damage in the tissues of gill, hepatopancreas and hemolymph were examined during the period of hypoxia and reoxygenation. The results indicated SOD activity, GPX activity, MDA concentration and DNA damage all increased basically compared with the control during the period of hypoxia except for MDA concentrations in the gill at 12 h and 24 h hypoxia (3.0 ppm), and these parameters were recovered to some degree during the period of reoxygenation. Moreover, the comet assays in the tissues of gill and hepatopancreas showed an obvious time- and dose-dependent response to hypoxia, which indicated comet assay in the two tissues could be used as sensitive biomarker to detect the occurrence of hypoxia. We conclude that acute hypoxia can induce oxidative stress, DNA damage and lipid peroxidation in the tissues of gill, hepatopancreas and hemolymph of L. vannamei and the DNA damage may come from hypoxia-induced oxidative stress. Highlights: SOD, GPX, MDA and DNA damage all increased compared with control during hypoxia. SOD, GPX, MDA and DNA damage were recovered to some degree during reoxygenation. DNA damage in gill and hepatopancreas showed a time- and dose-dependent response.